The phenomenon of caring by the midwife - A.G.W. Nolte (Curationis, 1992)
The child-bearing events are normal physiological processes in the body of the woman and embryo-foetus/baby. Many changes in the internal and external environments of the family take place, simultaneously with these normal processes. These changes lead to the development of certain tasks and responsibilities that must be successfully accomplished by the family during the child-bearing events. Many changes have also taken place in midwifery during the last half of this century. These changes in midwifery practice, together with the changes that take place during chi Id-bearing events, may cause the new family to feel insecure during this stage of their lives.